The Five Tool Negotiator - Korobkin, Russell (Ascent Audio, 2021)
The Five Tool Negotiator stands apart in a category saturated with breezy, self-help volumes as a highly researched must-have for anyone looking to improve their bargaining skills. Nationally renowned UCLA law professor Russell Korobkin distills insights drawn from his decades of studying and teaching the keys to successful negotiations into five simple-yet-sophisticated strategies: Bargaining Zone Analysis, Persuasion, Deal Design, Power, and Fairness Norms. Incorporating lively anecdotes and fascinating social science experiments, Korobkin brings to life concepts from the disparate fields of psychology, economics, and game theory. Designed for use at both the flea market and in the C-suite, this game-changing, universal approach provides a formula that a savvy listener can implement immediately. Throughout the book, Korobkin also meticulously explains how to answer questions that arise in every negotiation, including Should you make the first offer or let the other side go first?; What makes some proposals seem more fair than others?; and How do you decide whether to accept an offer, reject it, or make a counteroffer? Listeners will come away with a roadmap to becoming a truly complete negotiator, able to understand bargaining as both a strategic and social activity.